A New Strategy for Realizing the Conversion of "Homo–Hetero–Homo" Heteroepitaxial Growth in Bi2Te3 and the Thermoelectric Performance. Issue 19 (2nd April 2014) - Guo, Wei; Ma, Jianmin; Yang, Jiaqin; Li, Di; Qin, Qing; Wei, Caiying; Zheng, Wenjun
Abstract Uncovering the reason for structure‐dependent thermoelectric performance still remains a big challenge. A low‐temperature and easily scalable strategy for synthesizing Bi2Te3 nanostring hierarchical structures through solution‐phase reactions, during which there is the conversion of "homo–hetero–homo" in Bi2Te3 heteroepitaxial growth, is reported. Bi2Te3 nanostrings are obtained through the transformation from pure Bi2Te3 hexagonal nanosheets followed by TeBi2Te3 "nanotop" heterostructures to Bi2Te3 nanostrings. The growth of Bi2Te3 nanostrings appears to be a self‐assembly process through a wavy competition process generated from Te and Bi3+. The conversion of homo–hetero–homo opens up new platforms to investigate the wet chemistry of Bi2Te3 nanomaterials. Furthermore, to study the effect of morphologies and hetero/homo structures, especially with the same origin and uniform conditions on their thermoelectric properties, the thermoelectric properties of Bi2Te3 nanostrings and TeBi2Te3 heterostructured pellets fabricated by spark plasma sintering have been investigated separately.